Research Into Influence of Ultra- and Nanodisperse Size Additives on the Structure and Properties of Heat Insulating Autoclaved Aerated Concrete. (2017) - Leontev, Stepan; Saraykina, Kseniya; Golubev, Viktor; Yakovlev, Grigory; Rakhimova, Nailya; Shamanov, Vitaly; Senkov, Sergey; Urkhanova, Larisa
Abstract: The paper presents the results of the research into the influence of various ultra- and nanodisperse size additives on the structure and mechanical-and-physical properties of heat insulating autoclaved aerated concrete (AAC). Research into interaction mechanisms of such additives as silica gel, high active metakaolin and multi-walled carbon nanotube dispersion (MWCNTs) with heat insulating AAC components consisted in the evaluation of the dynamics of the cellular concrete plastic strength increase of porous mixture, degree of cellular concrete blowup and comparing the strength and density of the check sample and the modified one. The studies found that the most effective method of obtaining the structural strength of AAC is by the use of the MWCNTs. They contribute to obtaining the optimum viscoplastic properties of bulk concrete and stabilizing of the pore formation process with simultaneous formation of the solid homogeneous hexagonal structure.